PROCESSING STUDENT DATA USING A DATA WAREHOUSE - Fahmi, fahmi Nugraha (Universitas Utpadaka Swastika, 2023)
Lectures are activities carried out by a higher education institution. This activity involves several elements, including students, academics and lecturers. The result of the lecture process is the emergence of grades for each student according to the courses they take. In each semester, an evaluation of the lecture process can be carried out, including obtaining an index of the quality of lecturers and students. This information can be used by management in making policies regarding the lecture process in the future. Data warehouse technology is needed to manage all values and display them in a reporting system for management. Data warehouse technology is needed so that the information displayed can be presented in multi-dimensional form related to students, lecturers and grades.